Analisis User Interface dan User Experience pada Website Sekolah Tinggi Teknologi Adisutjipto Yogyakarta - Dwi Nugraheny (Institut Teknologi Dirgantara Adisutjipto, 2016)
User Interface Design and User Experience both on a website will make visitors want to linger on those websites. But otherwise, a User Interface Design and User Experience bad a website makes visitors leave the website. This study, will analyze the website at the College of Technology Adisutjipto (STTA) Yogyakarta from the point of view of the user interface and user experience that is part of the Human Computer Interaction (HCI), in order to evaluation and follow-up the website STTA to better meet expectations of users / visitors. The test result can be concluded that website STTA has Usability and Quality of Information is good, and Content, Pleasure, Classic Aesthetics, Expressive Aesthetics is enough